EVALUASI KESESUAIAN LAHAN SEBAGAI DASAR PERENCANAAN PENGEMBANGAN BEBERAPA TANAMAN PERTANIAN DI KECAMATAN PARIGI KABUPATEN MUNA - , LA MPIA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Land evaluation constitutes the process of assessing the potential land for the use of certain plants. This potential land can be utilized as a basis in planning of certain activities in agricultural plants developments. The objective of this research was to determine the land classification and to make the classification track of land until achieving the subgroup classes